2001
DOI: 10.1038/sj.bmt.1703082
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of standardized large volume leukapheresis (LVL) in patients do not show a recruitment phenomenon of peripheral blood progenitor cells (PBPC)

Abstract: Summary:Although several studies have demonstrated the efficacy of large volume leukapheresis (LVL) to yield high numbers of peripheral blood progenitor cells (PBPC), the mechanisms of stem cell release into circulation and the postulated phenomenon of PBPC recruitment during apheresis have not been investigated in detail. Therefore, we analyzed the kinetics of stem cell enrichment in a total of 34 standardized LVL for patients with hematologic malignancies (lymphoma, multiple myeloma) and solid tumors (breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 30 publications
(39 reference statements)
3
27
1
Order By: Relevance
“…The lowest CD34+ cell yield and collection efficiency were observed at the very beginning of LVL, which can be explained by the time required to establish interface, and by a dilution effect in the first collection bag, caused by the automated filling with saline [19,29,31]. In the remaining collection period, the CD34+ cell yield and collection efficiency were stable, without any time-dependent changes, as Bojanic,16 observed by others [9,10].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The lowest CD34+ cell yield and collection efficiency were observed at the very beginning of LVL, which can be explained by the time required to establish interface, and by a dilution effect in the first collection bag, caused by the automated filling with saline [19,29,31]. In the remaining collection period, the CD34+ cell yield and collection efficiency were stable, without any time-dependent changes, as Bojanic,16 observed by others [9,10].…”
Section: Discussionmentioning
confidence: 86%
“…The optimal study design would be to compare products collected during the same procedure at different time, which was done in this study, and differences caused by interindividual variability were excluded. Studies of kinetics of PBSC enrichment during LVL showed variable results [3,[8][9][10][19][20][21][22][23][24][25][26][27][28][29][30][31], which could be consequence of difference in volumes of processed blood. Therefore, processed blood volume in our study was standardized and strictly related to the patient's TBV.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 The number of circulating hematopoietic stem cells increases during the recovery phase of chemotherapy-induced myelosuppression, as well as after the administration of various cytokines and hematopoietic growth factors including granulocyte colony-stimulating factor (G-CSF). 2,8,9 Over the last two decades, clinical practices have taken advantage of these observations. However, increasing awareness of mobilization failure with G-CSF In Europe, the combination of plerixafor + granulocyte colony-stimulating factor is approved for the mobilization of hematopoietic stem cells for autologous transplantation in patients with lymphoma and myeloma whose cells mobilize poorly.…”
Section: Introductionmentioning
confidence: 99%
“…But recruitment has not been defined similarly by all the authors. Some authors have considered recruitment as a time-or blood process-dependent phenomenon consistent with a CD34 1 cell release in peripheral blood after the beginning of the apheresis (72,75,76,78). Some kind of PBPC mobilization by the procedure itself has been proposed, but it has not been demonstrated (72,75,77,78).…”
Section: Lvl and Recruitment Phenomenonmentioning
confidence: 96%